Analysing Informal Work Practices And Social Networks In The Workplace - lghomrore, Abome Sharp (Journal Integration of Management Studies, 2025)
This study investigates how social networks influence informal work practices in the workplace. Employee communication, teamwork, and knowledge sharing are greatly impacted by informal networks, which are made up of connections that do not fall under official organisational structures. This study uses the framework of social network theory to investigate how strong and weak relationships support information sharing, creativity, and problem-solving within an organisation. The impact of technology and remote work on social networks and informal practices, as well as the role of social networks in the workplace, are all highlighted in the study. The study also highlights possible issues that may occur in informal networks, like exclusion and information silos. To improve collaboration and innovation, organisations are advised to balance formal and informal practices, leverage informal leaders, and cultivate inclusive networks. In the end, social networks can be used to comprehend and maximise informal work practices, which can enhance employee engagement and organisational performance.